The Early Life Of Russell’s Notion Of A Propositional Function - Michael Beaney (Baltic International Yearbook of Cognition, Logic and Communication, 2008)
In this paper I describe the birth of Russell’s notion of a propositional function on 3 May 1902 (precise time of day unknown) and its immediate context and implications. In particular, I consider its significance in relation to the development of his views on analysis.
Keywords: philosophy; analytic philosophy